2011
DOI: 10.1097/ico.0b013e3181e2cf3f
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy of Combined Pre-Descemet Membrane Corneal Dystrophy and Fuchs Endothelial Dystrophy

Abstract: In vivo CM is a powerful tool in the study of rare corneal dystrophies and degenerations and nonprogressive or slowly progressive corneal disorders where there is a limited availability of corneal tissue for examination and when the final diagnosis is difficult to obtain with conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…We found that the activated keratocytes in the posterior stroma had enlarged cell bodies with a regular arrangement of hyperreflective particles inside. These IVCM findings were similar to the previous reports of isolated PDCD in the literatures [2, 11, 12]. In some other previous studies, the size and morphology of keratocytes in the posterior stroma were reported to be normal in isolated PDCD, although hyperreflective particles were also found in the intracellular and extracellular compartments [9, 10, 13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the activated keratocytes in the posterior stroma had enlarged cell bodies with a regular arrangement of hyperreflective particles inside. These IVCM findings were similar to the previous reports of isolated PDCD in the literatures [2, 11, 12]. In some other previous studies, the size and morphology of keratocytes in the posterior stroma were reported to be normal in isolated PDCD, although hyperreflective particles were also found in the intracellular and extracellular compartments [9, 10, 13].…”
Section: Discussionsupporting
confidence: 91%
“…However, other IVCM studies have found that the lesion of PDCD was involved in the whole thickness of the corneal stroma [9, 10, 13]. The involvement of corneal endothelial layer was also reported in some PDCD patients [2, 12]. In our present case, using IVCM, we found that the enlarged keratocytes with hyperreflective particles in the posterior stroma were consistent with the histopathological study.…”
Section: Discussionsupporting
confidence: 90%
“…32,4043 Between them, pleomorphic and polymegathic endothelial cells appeared hyperreflective and could not be identified individually. In the late stage, diffuse hyporeflective areas surrounded by hyperreflective endothelial cells were noted.…”
Section: Resultsmentioning
confidence: 96%
“…On slit-lamp examination, larger and more polymorphous opacities than those of Cornea Farinata or Fleck’s dystrophy are seen, distributed throughout the cornea but with a predilection for the deep stroma. 32 IVCM demonstrates intra- and extra-cellular hyper-reflective inclusions, pleomorphic in shape and size, measuring from 30 μm to 80 μm immediately anterior to Descemet’s membrane and prominent subbasal nerves (Figure 4). 30 The intracellular particles have been noted inside enlarged keratocytes with abnormally visible intercellular processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation